2021
DOI: 10.1249/mss.0000000000002629
|View full text |Cite
|
Sign up to set email alerts
|

Running Footstrike Patterns and Footwear in Habitually Shod Preschool Children

Abstract: IntroductionRunning skill develops during the preschool age. There is little research evidence as to how footstrike patterns are affected by footwear during this important developmental period.PurposeThe aim of this study was to compare footstrike patterns among different age groups of preschool children running in different footwear conditions.MethodsThree-dimensional kinetics and kinematics were collected while 48 typically developing children age 3 to 6 yr ran overground at self-selected speed in a barefoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 50 publications
(106 reference statements)
1
17
1
Order By: Relevance
“…Healthy, typically developing forty-eight Caucasian preschool children (26 boys and 22 girls aged 3-6 years) participated in this study. This is a further analysis from the data collection of children in the recent study where we reported changes in lower limb kinematics at footstrike in three different footwear conditions [13]. They were habitually shod and came from the Moravian-Silesian region in Czech Republic.…”
Section: Participantsmentioning
confidence: 95%
See 4 more Smart Citations
“…Healthy, typically developing forty-eight Caucasian preschool children (26 boys and 22 girls aged 3-6 years) participated in this study. This is a further analysis from the data collection of children in the recent study where we reported changes in lower limb kinematics at footstrike in three different footwear conditions [13]. They were habitually shod and came from the Moravian-Silesian region in Czech Republic.…”
Section: Participantsmentioning
confidence: 95%
“…Based on the research in adult populations, we hypothesized that running barefoot and in minimalist shoes would lead to lower impact forces and loading compared to standard running shoes in all age groups of preschool children [10,21,24]. However, as recent research in preschoolers showed that 3-and 4-year-old children did not change their footstrike pattern (remained rearfoot-midfoot strike) according to footwear condition as 5-and 6-year-old who displayed a similar reaction to adults runners (shifted to forefoot strike in barefoot and minimalist) [13]. Therefore, we hypothesized that higher impact loading in barefoot and minimalist shoes compared standard running shoes in younger children, but lower in the older children.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations